2022
DOI: 10.1002/advs.202105769
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Friction in Intertwined Structures for High‐Capacity Reusable Energy‐Absorbing Architected Materials

Abstract: Energy-absorbing materials with both high absorption capacity and high reusability are ideal candidates for impact protection. Despite great demands, the current designs either exhibit limited energy-absorption capacities or perform well only for one-time usage. Here a new kind of energy-absorbing architected materials is created with both high absorption capacity and superior reusability, reaching 10 kJ kg −1 per cycle for more than 200 cycles, that is, unprecedentedly 2000 kJ kg −1 per lifetime. The extraord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…[57] Based on these data, it was confirmed that the 3D gel structure could be restored to its original state after breakdown. Considering these attractive rheological properties, the magnetic fluid was further absorbed into a porous elastic polyurethane sponge to be used as the buffer material, [58,59] and falling ball impact tests were further performed to evaluate the energy dissipation and impact mitigation capability of the magnetic fluid/sponge composite under dynamic loading. As shown in Figure S10, Video S1 (Supporting Information), compared with the blank sponge, the magnetic fluid adsorbed sponge after heating was superior in protecting the glass slide under severe dynamic loading, which also exhibited good shock absorption ability.…”
Section: Resultsmentioning
confidence: 99%
“…[57] Based on these data, it was confirmed that the 3D gel structure could be restored to its original state after breakdown. Considering these attractive rheological properties, the magnetic fluid was further absorbed into a porous elastic polyurethane sponge to be used as the buffer material, [58,59] and falling ball impact tests were further performed to evaluate the energy dissipation and impact mitigation capability of the magnetic fluid/sponge composite under dynamic loading. As shown in Figure S10, Video S1 (Supporting Information), compared with the blank sponge, the magnetic fluid adsorbed sponge after heating was superior in protecting the glass slide under severe dynamic loading, which also exhibited good shock absorption ability.…”
Section: Resultsmentioning
confidence: 99%
“…Interpenetrating lattice designs have recently been explored as alternatives to interconnected design (34,35), showing the potential to achieve multifunctionality while being composed of mostly two interconnected lattices. Exploiting friction between structural members has also been shown as a method to absorb energy without accumulating substantial damage (36)(37)(38)(39), but most designs lack hierarchy to further augment their properties. A different hierarchical design framework has been introduced, in which multiple interweaving fibers are arranged into effective beams within a microlattice that contains no junctions (40).…”
Section: Introductionmentioning
confidence: 99%
“…Rivera found that at the submillimeter level, a suture structure exists in the elytra of P diabolicus. This suture structure can effectively prevent collapse failure of the structure when the elytra are compressed. Sutures can be found in a variety of unrelated biological groups, such as woodpecker beaks, turtle shells, , nacre, bone, and plant seeds. This interface mechanism has attracted significant interest from the engineering and material science communities. , …”
Section: Introductionmentioning
confidence: 99%